Contemporary Mythopoiesis: the role of Herodotus in Neil Gaiman's American Gods. (17th April 2020) - Zajko, Vanda
Abstract: This article explores Neil Gaiman's transmedial work American Gods as an example of contemporary mythmaking. Published in novel form in 2001 and launched as a television series in 2017, American Gods provides a commentary on the connectedness between different systems of stories and on myth itself as a vital present-day cultural form. It also provides us with a model for repurposing ancient material without reproducing the traditional hierarchies associated with cultures of storytelling. Gaiman's text is an interesting case-study from the perspective of classical reception because he sidelines the ancient Greek gods in the main body of his story, while simultaneously positioning the ancient historian Herodotus as a significant intertext. The process of evaluating different cultures often veers between analyses which focus on similarities manifested across place and time and those which espouse a form of cultural relativism, a 'live and let live' philosophy. Gaiman seems to be offering something else here, namely a more vital and connected model for co-existence, one which is moving towards a pluri-versal perspective that acknowledges the links between political power, knowledge, and identity.